2022
DOI: 10.1039/d2ta00545j
|View full text |Cite
|
Sign up to set email alerts
|

Atomistic insight into the dopant impacts at the garnet Li7La3Zr2O12 solid electrolyte grain boundaries

Abstract: The atomic-scale impact of dopants at the grain boundary (GB) of the Li7La3Zr2O12 solid electrolyte is revealed by the first-principles calculation. The preferential sites of dopants, ion diffusions, Li interstitial stabilities and phase segregations at doped GBs are uncovered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 64 publications
0
26
0
Order By: Relevance
“…calculated that it was possible for LaAlO 3 to form at the grain boundaries, as well. 42 With this in mind, the increased presence of secondary grain boundary phases appears to be the cause of the increased observation of intergranular fracture at the LLZO–Al0.55 composition as compared to the largely intragranular fracture in the other three compositions (Fig. S2†).…”
Section: Resultsmentioning
confidence: 91%
See 4 more Smart Citations
“…calculated that it was possible for LaAlO 3 to form at the grain boundaries, as well. 42 With this in mind, the increased presence of secondary grain boundary phases appears to be the cause of the increased observation of intergranular fracture at the LLZO–Al0.55 composition as compared to the largely intragranular fracture in the other three compositions (Fig. S2†).…”
Section: Resultsmentioning
confidence: 91%
“…In LLZO, aluminum preferentially substitutes for lithium at the 24d tetrahedral site, and secondarily in the 96h and 48g sites. 19,23,42,45,54 It is believed that once the energetically favorable sites have been filled to their maximum aluminum capacity and the solubility limit is reached, the excess aluminum forms aluminum-rich secondary phases, such as LaAlO 3 . 21,37 As was mentioned above, it is commonly observed that La 2 Zr 2 O 7 forms due to lithium loss.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations